Dissemination of Clostridium difficile spores between environment and households: Dog paws and shoes. (23rd April 2018) - Janezic, Sandra; Mlakar, Sabina; Rupnik, Maja
Summary: Clostridium difficile is an anaerobic, spore‐forming bacterium that causes intestinal infections. Although C. difficile is still predominantly considered as a nosocomial pathogen, there has been an increase in the number of community‐associated infections. Since C. difficile is ubiquitous and can be isolated from nearly any environment, one of the possibilities for community acquisition could be exposure to spores in the domestic environment. The aim of this study was to evaluate the presence of C. difficile spores on shoes, slippers and on dog paws and to explore the importance of these surfaces as vectors for the dissemination of C. difficile in a domestic environment. Overall, C. difficile was present in 14 (70%) of 20 households and in 31 of 90 (34%) collected samples. Shoes and slippers had the highest positivity rates, 19 of 44 (43%) and 6 of 21 (28%), respectively, followed by dog paws 6 of 25 (24%). Thirteen C. difficile PCR ribotypes were identified with half of the isolates belonging to ribotype 014/020, which is the predominant type circulating in human population and is also commonly found in the environment (e.g. soil and water) in Slovenia. In three households, identical PCR ribotypes were found on dog paws, shoes and slippers. To understand the fine‐scale genetic relatedness of these isolates, we sequenced the genomes. Low level of single nucleotide variant (SNV) differences between isolates from the same households, consistent with a recent transmission from a common source, were seen for isolates of PCR ribotype 014/020 but not for PCR ribotype 010. Our results suggest that shoe soles and dog paws could serve for the dissemination of C. difficile spores between households and environment and could contribute to community‐relevant sources for C .  difficile infection in humans.